Meningkatkan Kemampuan Membaca Pada Anak Sekolah Dasar Menggunakan Program Mobile Teaching - Floren Br. Barus; Fajar Utama Ritonga; Bengkel Ginting (Universitas Muhammadiyah Enrekang, 2023)
The ability to read in children is an ability that is very necessary because reading ability is an initial ability that greatly influences skills, where if reading ability is not strong then other skills will also be difficult to manage. So that this is a matter that really needs to be considered by educators or the board of teachers and even parents to find ways to overcome the problems of children who have difficulty reading. In this case creativity is needed as well as inspiration for educators to maximize innovative efforts so that children can improve their reading skills. So an innovative program was formed which is expected to achieve a goal in the form of increasing reading skills in children. The program in question is the Mobile Teaching program which is an educator program in which an educator goes directly to help students understand the lesson. The Mobile Teaching technique is a technique that is carried out by means of educators trying to teach more closely to students, and going around to find out the situation of the class and students while studying. With these efforts it is hoped that children can feel more intense in learning with educators so that they can ask questions directly without hesitation to educators. This is expected to increase the effectiveness of teaching and learning activities. In solving this problem the program implementation method is also collaborated with social work methods starting from the assessment stage to termination.